Stable models for infinitary formulas with extensional atoms. Issue 5 (14th October 2016) - HARRISON, AMELIA; LIFSCHITZ, VLADIMIR
Abstract: The definition of stable models for propositional formulas with infinite conjunctions and disjunctions can be used to describe the semantics of answer set programming languages. In this note, we enhance that definition by introducing a distinction between intensional and extensional atoms. The symmetric splitting theorem for first-order formulas is then extended to infinitary formulas and used to reason about infinitary definitions.